Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan Dalam Meningkatkan Loyalitas Pelanggan Pada Tv Kabel Amaco Media Landasan Ulin Banjarbaru - Rizky Subhan; Dwi Wahyu A; Maryono Maryono (Universitas Lambung Mangkurat, 2019)
Multimedia is one of the very superior facilities in the world of information, both at national and international levels. One form of multimedia is telivisi. On average every home, office, restaurant, hotel and others definitely have telivisi. Amaco media Ulin foundation is engaged in pay tv services, up to now has amounted to 587 customers.This study aims to examine the effect of Service Quality (X1), Price (X2), with Customer Subscriber Intervention (Z) intervention variable on customer loyalty (Y) on Cable TV customer Amaco Media Platform Ulin Banjarbaru.Samples taken in this study were 238 customers by using slovin formula. Furthermore, data collection techniques with questionnaires and questionnaire division techniques with proportionate stratifed random sampling. And for data analysis in this research use Smart PLS version 2.0 M3.The result of the research indicates that 1) the quality of service influence to satisfaction 2) price influence to satisfaction 3) satisfaction influence to loyalty 4) service quality influence to loyalty 5) price influence to loyalty. Simultaneously, the influence of service quality and price to satisfaction is 79,9% and the influence of service quality and price to loyalty is 74,1%. Keywords: quality of service, price, customer satisfaction, customer loyalty